Modern and optimized planning tool for microwave link design - Damião, M. (2014)
The microwave link planning tool described in this paper, named as Smart Link Planning Tool (SLPT), is a wireless communication planning tool for radio point-to-point communications, using microwave links (ML). This tool was firstly developed with the aim of helping telecommunication students, on their procedures to study and plan a ML and it was developed in a modern programming language, Java, to facilitate its continuous improvement and modernization on different platforms. SLPT interacts with a geographic information system (GIS) and Google maps (GM), with a modern, intuitive and user-friendly interface which facilitates tasks such as the placement of the transmitter and receiver positions and the adequate number of repeaters along the path. It has the ability to show in real time the evolution of all calculations and the implications of the choices taken by the user towards optimization. The SLPT implements the latest standards and recommendations of the International Telecommunications Union (ITU), namely their radio counterpart (ITU-R), so the planned links obey these mandatory international regulations.